Return to sport or work following surgical management of scapholunate ligament injury: a systematic review. Issue 12023 (1st December 2022) - Liew, Mei Yen; Dingle, Lewis A; Semple, Abi; Rust, Philippa A
Abstract: Introduction: This systematic review aims to compare the rate and time to return to sport or work following surgical interventions for isolated scapholunate ligament (SLL) injury. Sources of data: A PRISMA-compliant systematic search of Medline, EMBASE, Cochrane, AMED, CINAHL Plus and SPORTDiscus was performed using keywords 'scapholunate', 'scapholunate ligament', 'scaphoid lunate', 'sport', 'sport injury', 'athlete', 'athletic performance', 'elite', 'return to sport', 'training', 'work', 'activity', 'return to activity'. Adult patients with isolated SLL injury, without osteoarthritis, were included. Areas of agreement: Fourteen papers, including six different surgical interventions, met the criteria for the final analysis. All surgical techniques demonstrated acceptable rates of return to work or sport (>80%). Areas of controversy: The optimal surgical intervention for isolated SLL injury remains undetermined due to heterogeneity and limited sample sizes of published studies. Growing points: This systematic review has provided clarification on the available literature on treatment modalities for isolated SLL injuries in the absence of osteoarthritis. Areas timely for developing research: Prospective, randomized, primary studies are needed to establish optimal treatment for acute isolated SLL injuries.